Function of a Principal Na(+)/H(+) Antiporter, ShaA, Is Required for Initiation of Sporulation in Bacillus subtilis - Kosono, Saori (American Society for Microbiology, 2000)
ShaA (sodium/hydrogen antiporter, previously termed YufT [or NtrA]), which is responsible for Na(+)/H(+) antiporter activity, is considered to be the major Na(+) excretion system in Bacillus subtilis. We found that a shaA-disrupted mutant of B. subtilis shows impaired sporulation but normal vegetative growth when the external Na(+) concentration was increased in a low range. In the shaA mutant, ς(H)-dependent expression of spo0A (P(S)) and spoVG at an early stage of sporulation was sensitive to external NaCl. The level of ς(H) protein was reduced by the addition of NaCl, while the expression of spo0H, which encodes ς(H), was little affected, indicating that posttranscriptional control of ς(H) rather than spo0H transcription is affected by the addition of NaCl in the shaA mutant. Since this mutant is considered to have a diminished ability to maintain a low internal Na(+) concentration, an increased level of internal Na(+) may affect posttranscriptional control of ς(H). Bypassing the phosphorelay by introducing the sof-1 mutation into this mutant did not restore spo0A (P(S)) expression, suggesting that disruption of shaA affects ς(H) accumulation, but does not interfere with the phosphorylation and phosphotransfer reactions of the phosphorelay. These results suggest that ShaA plays a significant role at an early stage of sporulation and not only during vegetative growth. Our findings raise the possibility that fine control of cytoplasmic ion levels, including control of the internal Na(+) concentration, may be important for the progression of the sporulation process.